2011
DOI: 10.2967/jnumed.111.094375
|View full text |Cite
|
Sign up to set email alerts
|

Bombesin Antagonist–Based Radioligands for Translational Nuclear Imaging of Gastrin-Releasing Peptide Receptor–Positive Tumors

Abstract: The chelators do influence the affinity, antagonistic potency, and pharmacokinetics of the conjugates. The promising preclinical results warrant clinical translation of these probes for SPECT and PET.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
119
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(130 citation statements)
references
References 25 publications
11
119
0
Order By: Relevance
“…This finding was also extended to GRPR antagonists, with the seminal work of Cescato et al (11). Recently, more articles have appeared showing the promise of novel radiolabeled GRPR antagonists for GRPR-positive tumor imaging (12,(16)(17)(18)25). The studies revealed favorable pharmacokinetics of radiolabeled antagonists, including high tumor uptake and fast clearance from nontargeted tissues.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This finding was also extended to GRPR antagonists, with the seminal work of Cescato et al (11). Recently, more articles have appeared showing the promise of novel radiolabeled GRPR antagonists for GRPR-positive tumor imaging (12,(16)(17)(18)25). The studies revealed favorable pharmacokinetics of radiolabeled antagonists, including high tumor uptake and fast clearance from nontargeted tissues.…”
Section: Discussionmentioning
confidence: 92%
“…Several GRPR antagonists have since been developed by the modification of C-terminal residues of GRPR agonists, including the statinbased BBN analog, JMV594 (H-D-Phe-Gln-Trp-Ala-Val-GlyHis-Sta-Leu-NH 2 ) (15). 68 Ga-labeled GRPR antagonists were developed for PET imaging, showing good targeting properties in preclinical studies (12,(16)(17)(18) and recently also in clinical trials (19,20). Clinical evaluation of the 68 Ga-labeled GRPR antagonist BAY86-7548 ( 68 Ga-DOTA-4-amino-1-carboxymethylpiperidine-D-Phe-Gln-TrpAla-Val-Gly-His-Sta-Leu-NH 2 ) has shown a specificity, sensitivity, and accuracy of 88%, 81%, and 83%, respectively, for the detection of primary PCa.…”
mentioning
confidence: 99%
“…Bombesin analog NOTA-PEG 2 -[D-Phe 6 ,Sta 13 ,Leu 14 ]bombesin [6][7][8][9][10][11][12][13][14] (further denoted as NOTA-P2-RM26, see Chart) was synthesized by standard manual solid-phase peptide synthesis 17 as described in Supplementary material 1.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…It has been demonstrated earlier that positively charged at the N-terminus bombesin agonists exhibit higher affinities to the GRP receptors, while a negative charge decreases the affinity. 12,22 The overall charge of a complex of dianionic NOTA with indium or gallium is +1. This positive charge can explain the more than 4-fold lower IC 50 values for metal loaded analogs compared with non-loaded peptide in our study.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation